2013
DOI: 10.1088/0029-5515/53/11/113016
|View full text |Cite
|
Sign up to set email alerts
|

Edge microstability of NSTX plasmas without and with lithium-coated plasma-facing components

Abstract: The pedestal structure in NSTX is strongly affected by lithium coatings applied to the PFCs. In discharges with lithium, the density pedestal widens, and the electron temperature (Te) gradient increases inside a radius of ψN ∼ 0.95, but is unchanged for ψN > 0.95. The inferred effective electron thermal and particle profiles reflect the profile changes: is slightly increased in the near-separatrix region, and is reduced in the region ψN < 0.95 in the with-lithium case. The profile shows a broadening of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
80
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(91 citation statements)
references
References 42 publications
(77 reference statements)
10
80
1
Order By: Relevance
“…The difference between the study reported herein and the work of Ref. 16 is the change in the plasma shaping and the lithium dose that altered the pedestal structure. Here also, the suppression of ELMs and the flattening of the edge density profiles are observed from the lithiated experimental data.…”
Section: Introductioncontrasting
confidence: 77%
See 3 more Smart Citations
“…The difference between the study reported herein and the work of Ref. 16 is the change in the plasma shaping and the lithium dose that altered the pedestal structure. Here also, the suppression of ELMs and the flattening of the edge density profiles are observed from the lithiated experimental data.…”
Section: Introductioncontrasting
confidence: 77%
“…It was also concluded in Ref. 16 that the decrease in the pedestal top energy transport and the widening of the pedestal region in lithiated discharges were related to the stabilization of MT modes by density gradients. The suppression of ELMs in lithiated discharges may be explained by the stiffness of the electron temperature profile due to unstable ETG modes coupled with the strong reduction in the electron density, when compared to a non-lithiated discharge.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Experimentally, fluctuations have been diagnosed that are consistent with MTM [22,23,25], KBM [22,[24][25][26], and trapped electron modes (TEM) [22], while linear gyrokinetic modeling has identified MTM [19,[27][28][29][30], TEM [30,31], ETG [29,30,32,33], KBM [19,26,27,29,30,34,35], and unidentified drift waves [36]. Due to the large number of possible instabilities, and the complexity of the nonlinear turbulent state (that reflects the underlying instabilities in not so obvious ways), no clear picture has emerged regarding the relative importance of these modes for pedestal transport.…”
Section: Pacs Numbersmentioning
confidence: 92%